ASSOCIATION OF LPL-HINDIII POLYMORPHISM WITH CORONARY ARTERY DISEASE IN MACEDONIAN POPULATION - Georgiev, Antonio (Association of medical doctors „Sanamed” Novi Pazar, 2013)
Objective: Coronary artery disease (CAD) is a leading cause of high mortality and morbidity in worldwide. The HindIII polymorphism of the LPL gene (LPL-HindIII) is a common variant and has been associated with plasma lipid and lipoprotein variability in population studies. Aim: Evaluation of the LPL-HindIII polymorphism as an independent risk factor for coronary artery disease in Macedonian population. Material and Methods: Apolymerasechainreaction amplification and consecutive restriction enzyme digestion was used to reveal lipoprotein lipase, the intron 8 LPL-HindIII polymorphism. Study group included 114 randomized subjects with angiographically documented coronary artery stenosis (CAD group: 87 males, 27 females). Control group consisted of 35 patients (21 males and 14 females) without significant stenosis in coronary arteries. Results: Independent multiple regression analysis of LDLplasma level and their correlation with LPL-HindIII polymorphism and analyzed risk factors: hypertension, diabetes, family history of CAD, physical activity, antilipidemic drugs and alcohol consumption, LDL, show statistically significant correlation with BMI, and also between LPL-HindIII and LDLplasma level. In the examined group, only triglycerides reached a statistically significant association with the LPL-HindIII polymorphism. Conclusion: In our study, the LPL-HindIII polymorphismwasnotidentified as independent risk factor for CAD, but showed association with high triglycerides and LDLlevels.
Keywords: coronary artery disease; DNA analysis; LPL-HindIII polymorphism